Twinning in Zr-Based Metal-Organic Framework Crystals - Sigurd Øien-Ødegaard; Karl Petter Lillerud (Chemistry, 2020)
Ab initio structure determination of new metal-organic framework (MOF) compounds is generally done by single crystal X-ray diffraction, but this technique can yield incorrect crystal structures if crystal twinning is overlooked. Herein, the crystal structures of three Zirconium-based MOFs, that are especially prone to twinning, have been determined from twinned crystals. These twin laws (and others) could potentially occur in many MOFs or related network structures, and the methods and tools described herein to detect and treat twinning could be useful to resolve the structures of affected crystals. Our results highlight the prevalence (and sometimes inevitability) of twinning in certain Zr-MOFs. Of special importance are the works of Howard Flack which, in addition to fundamental advances in crystallography, provide accessible tools for inexperienced crystallographers to take twinning into account in structure elucidation.